Peninfluence Word of Mouth, Brand Image, and Physical Evidence Consumer Satisfaction and Purchase Decision of Madura Tuna Fish Petis in Pamekasan - Wahyuni, Ratna Dwi; Munajah, Siti; Fianto, Achmad Yanu Alif (PT Inovasi Pratama Internasional, 2025)
This research aims to analyze the influence of Word of Mouth (WOM), Brand Image, and Physical Evidence on Consumer Satisfaction and Purchase Decisions for typical Madurese tuna fish paste products in Pamekasan. The research method used is a quantitative approach through surveys with multiple linear regression analysis. The research results show that WOM, Brand Image, and Physical Evidence significantly influence consumer satisfaction. Positive WOM has a strong influence in increasing consumer trust and expectations, while a Brand Image that highlights local culture increases the emotional value of the product. Meanwhile, physical evidence such as attractive and hygienic packaging plays an important role in forming perceptions of quality. Consumer satisfaction functions as a mediator that strengthens the relationship between independent variables and purchasing decisions. Satisfied consumers tend to make repeat purchases and provide positive recommendations to others. The implications of this research underscore the importance of marketing strategies that focus on managing WOM, strengthening brand image, and improving the quality of physical product elements to support loyalty and market growth.